Emotional Reactivity and Emotion Regulation Among Young Adults During COVID-19 Lockdown: The Moderating Role of Gender and Engagement in Sports - Mladenović, Marijana; Stojanović, Nikola; Stojanović, Darko; Živković, Mladen; Aleksić, Dragana; Tešanović, Gorana; Momčilović, Vladimir (Frontiers in Psychology, 2021)
The effects of the COVID-19 pandemic on mental health have not been fully inspected among the young adults' population. The objectives of the present study were: (1) to examine differences in emotional reactivity and emotion regulation between, both gender and sports engagement level during the first two weeks of the lockdown; and (2) to examine the possible impact of emotion regulation on emotional reactivity, and possible significant roles of gender and sports engagement level as moderators. This cross-sectional study included 315 Serbian young adults (aged 18-26 years old) during COVID-19 lockdown. Respondents answered socio-demographic questions and the Serbian version of the Multidimensional Emotion Questionnaire (MEQ). The results of confirmatory factor analysis indicated good fit for both positive and negative reactivity scales (SRMR = .037; CFI = .984, RMSEA = .046 and SRMR = .055; CFI = .964, RMSEA = .064, respectively). Gender differences were found in both positive (p = .039; d = 0.28) and negative emotional reactivity scales (p < .001; d = 0.60), with females reported lower and higher values, respectively. Professional athletes presented higher scores in positive reactivity scale in comparison to non-athletes (p < .001; d = 0.78) and recreational athletes (p = .034; d = 0.34) during two weeks of COVID-19 lockdown. Conversely, professional athletes scored lower in negative emotional reactivity scale in comparison to non-athletes (p < .001; d = 0.85) and recreational athletes (p = .006; d = 0.42). Both gender and sports engagement level differences were found for negative, but not for positive emotion regulation scale. Furthermore, results showed that engagement in sports level plays a significant role as moderator in relationship between negative regulation and negative reactivity, where professional athletes presented significant interaction effect and predicted lower negative reactivity scores compared to non-athletes and recreational athletes. However, gender does not moderate the influence of emotion regulation on emotional reactivity either positive or negative. Engagement in sports as a lifestyle may contribute to better emotional harmony especially in the crisis situation as COVID-19 lockdown.